Flow instabilities in two-phase or supercritical crust fluids and its possible relevance to seismoelectromagnetic disturbances - Yagova, Nadezda V.; Yagov, Viktor V.; Sinha, Ashwini K.; Hayakawa, Masashi; Fedorov, Evgeny N.; Vichare, Geeta (My University, 2018)
Flow pulsations in two-phase and single-phase near-critical fluids are considered as a possible source of ultra-low-frequency seismo-electromagnetic variations. The conditions for generation and suppression of density wave instability in the crust are analyzed and the surface electromagnetic effect due to streaming potential generation is estimated. The upper limit of amplitude of magnetic field variations due to density wave instability is about 0.1 nT for single-phase supercritical and 1 nT for two-phase flow oscillations in the frequency range 104102 Hz for the temperature gradients and spatial scales possible during strike slip events. The signal is characterized by a decaying amplitude with typical relaxation time of about several quasi-periods. The possibility of generation of very lowfrequency flow pulsations in two-phase fluids via individual bubble evolution and interaction with external acoustic waves is discussed.
Keywords: Seismo-electromagnetics; Two-phase fluid; Electrokinetic effect